1982
DOI: 10.1111/j.1432-1033.1982.tb06494.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Sulfate with Carbonic Anhydrase

Abstract: 1. In the absence of sulfate the pH/rate profile for the 4-nitrophenyl acetate hydrolase activity of bovine carbonic anhydrase is complex. The results fit with a microscopic ionization scheme involving two electrostatically interacting groups. The activity depends on the concentration of the basic form of one of these groups. Proton N M R spectra show that the active site residue, His-64, has titration behaviour corresponding to that of the second group of the ionization scheme.2. The addition of increasing co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 34 publications
6
35
0
Order By: Relevance
“…In contrast, spectroscopic and kinetic studies have suggested sulfate binding to both native and cobalt-substituted carbonic anhydrase (Lindskog, 1982;Simonsson & Lindskog, 1982;Pocker & Miao, 1987;Bertini, Canti, Luchinat & Scozzafava, 1977). Simonsson & Lindskog (1982) found that the esterase inhibition of sulfate never exceeded 20%, since the dissociation constant apparently increased with increasing sulfate concentration (ionic strength). Such a low degree of binding is difficult to observe crystallographically.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, spectroscopic and kinetic studies have suggested sulfate binding to both native and cobalt-substituted carbonic anhydrase (Lindskog, 1982;Simonsson & Lindskog, 1982;Pocker & Miao, 1987;Bertini, Canti, Luchinat & Scozzafava, 1977). Simonsson & Lindskog (1982) found that the esterase inhibition of sulfate never exceeded 20%, since the dissociation constant apparently increased with increasing sulfate concentration (ionic strength). Such a low degree of binding is difficult to observe crystallographically.…”
Section: Discussionmentioning
confidence: 99%
“…The I,,, values correspond to the concentrations giving 50% inhibition. (Simonsson and Lindskog, 1982) and the dissociation constant for C1-is 190 mM at pH 6.8 (Behravan et al, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…The pH/rate profile for this esterase activity shows a ply, of 6.7 (Fig. 41, whereas the corresponding value for human isozyme I1 is 6.8 [33].…”
Section: Discussionmentioning
confidence: 99%